2016
DOI: 10.1371/journal.pmed.1001938
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Artesunate for Severe Malaria in African Children: A Multicenter Randomized Controlled Trial

Abstract: BackgroundCurrent artesunate (ARS) regimens for severe malaria are complex. Once daily intramuscular (i.m.) injection for 3 d would be simpler and more appropriate for remote health facilities than the current WHO-recommended regimen of five intravenous (i.v.) or i.m. injections over 4 d. We compared both a three-dose i.m. and a three-dose i.v. parenteral ARS regimen with the standard five-dose regimen using a non-inferiority design (with non-inferiority margins of 10%).Methods and FindingsThis randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…Any new medicine would therefore have to free up the microvasculature, either by disengaging or killing the parasites; the drug’s speed of onset of activity is therefore of paramount concern. The AQUAMAT and SEAQUAMAT studies that compared intravenous artesunate and intravenous quinine [74, 75] and other studies that compared intravenous or intramuscular artesunate [76, 77] showed that injected artesunate reduces the overall severe malaria patient mortality by between a third and a quarter. From a safety viewpoint, quinine use has been associated with injection-site pathologies, cinchonism [78, 79] and also risks of hypoglycemia.…”
Section: Severe Malariamentioning
confidence: 99%
“…Any new medicine would therefore have to free up the microvasculature, either by disengaging or killing the parasites; the drug’s speed of onset of activity is therefore of paramount concern. The AQUAMAT and SEAQUAMAT studies that compared intravenous artesunate and intravenous quinine [74, 75] and other studies that compared intravenous or intramuscular artesunate [76, 77] showed that injected artesunate reduces the overall severe malaria patient mortality by between a third and a quarter. From a safety viewpoint, quinine use has been associated with injection-site pathologies, cinchonism [78, 79] and also risks of hypoglycemia.…”
Section: Severe Malariamentioning
confidence: 99%
“…We suggest that drug-induced pitting should be evaluated early in the development of new generations of antimalarial molecules such as spiroindolones [11], which have an effect on ring circulating forms. This would help better grasp their mode of action in vivo, which helps predict the risk of posttreatment hemolysis observed in severe [4,[12][13][14] and more recently in uncomplicated malaria [9,15]. In the context of artemisinin resistance in Southeast Asia characterized by slow parasite clearance, a specific study on the role of pitting may explain how parasites initially escape clearance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria is transferred to human through a female Anopheles' mosquito (WANG; JACOBS-LORENA, 2017). During malaria hematological and biochemical changes take place due to which the infection become more severe (KREMSNER et al, 2016). White blood cell (WBC) count remains constant while lactate dehydrogenase increases in malarial patients.…”
Section: Introductionmentioning
confidence: 99%